Spatiotemporal calcium dynamics orchestrate oligodendrocyte development and myelination - Li, Jiaxing; Fiore, Frédéric; Monk, Kelly R.; Agarwal, Amit (Trends in neurosciences, 2025)
Oligodendrocyte lineage cells (OLCs), comprising oligodendrocyte precursor cells (OPCs) and oligodendrocytes, are pivotal in sculpting central nervous system (CNS) architecture and function. OPCs mature into oligodendrocytes, which enwrap axons with myelin sheaths that are critical for enhancing neural transmission. Notably, OLCs actively respond to neuronal activity, modulating neural circuit functions. Understanding neuron-OLC interactions is key to unraveling how OLCs contribute to CNS health and pathology. This review highlights insights from zebrafish and mouse models, revealing how synaptic and extrasynaptic pathways converge to shape spatiotemporal calcium (Ca2+) dynamics within OLCs. We explore how Ca2+ signal integration across spatial and temporal scales acts as a master regulator of OLC fate determination and myelin plasticity.